SOCIAL MEDIA, DIGITAL LITERACY, AND MULTICULTURAL ISLAMIC EDUCATION: PERSPECTIVES OF ISLAMIC HIGHER EDUCATION STUDENTS IN NORTH SUMATRA - Ahmad Ibrahim Hasibuan; Mulkan Hasibuan; Salma Rozana; Fatima Rahma Rangkuti (Referensi Islamika: Jurnal Studi Islam, 2025)
This study examines the relationship between social media use, Islamic digital literacy, and multicultural Islamic education from the perspective of students at Islamic higher education institutions (PTAI) in North Sumatra, Indonesia. This study employed a qualitative phenomenological approach. Data were collected through semi-structured in-depth interviews, participatory observation, and documentation involving 24 students (purposive sampling) from four purposively selected PTAI representing institutional diversity. Thematic saturation was continuously monitored and reached after the 20th interview, confirmed by 4 additional interviews yielding no new themes. Data analysis followed the Miles, Huberman, and Saldana (2014) interactive model, with source and method triangulation to ensure credibility. The study adhered to the SRQR (Standards for Reporting Qualitative Research) guidelines. Students demonstrated high technical digital skills but low critical literacy, particularly in evaluating religious content online. Social media simultaneously broadened multicultural awareness and intensified perceived religious exclusivism through students’ reported experiences of algorithmic echo chamber effects. Digital content significantly shaped students’ perceived tolerance attitudes. None of the four campuses had developed systematic institutional strategies for fostering digital religious moderation. The study is limited to four campuses in North Sumatra, which restricts the generalizability of findings to other regional and institutional contexts. The qualitative cross-sectional design does not allow for causal claims regarding attitudinal change over time. Practically, this study offers concrete implications for Islamic higher education institutions: curriculum reform through formal integration of Islamic digital literacy courses guided by the IDLT framework; development of digital religious moderation programs at the institutional level; investment in TPACK-based lecturer training for Islamic digital pedagogy; and structured programs to develop students’ critical digital literacy competencies. Future research employing mixed methods with a broader national sample is strongly recommended, as is quantitative validation of the IDLT framework across diverse PTAI contexts.  This study makes an original contribution by integrating Islamic digital literacy, multicultural education, and religious moderation within the PTAI context of North Sumatra. It proposes the Islamic Digital Literacy Triad (IDLT) as a conceptual framework for PTAI curriculum development, building upon existing digital literacy models by explicitly integrating Islamic ethical principles (tabayyun, wasathiyyah) and multicultural awareness as inseparable dimensions of digital competence within the Islamic higher education context.